FEMALE EXISTENTIAL PREDICAMENT IN JAI NIMBKAR’S NOVEL COME RAIN - Sonawane, Tejal (International Journal of Research -GRANTHAALAYAH, 2025)
The female existential predicament symbolizes and has reference to the unique challenges and struggles women face in defining their existence and purposes within patriarchal societies. These challenges have their roots in societal expectations, bias discrimination of gender and struggle to establish self. The galaxy of women writers has been dealing with feminine issues which were not given attention to in the male dominated society. The woman was considered not as a human being but a slave to do the household things and a child producing machine. Her individuality, necessities, likings attitudes were not given any importance, she was treated as if she did not exist. The female self was obliterated and her identity reconstructed to fit and support masculine fantasy framework.